Spectroscopic study of lipase from Candida rugosa immobilized onto calcined layered double hydroxides - Abdul Rahman, Mohd Basyaruddin; Md. Yunus, Noor Mona; Basri, Mahiran; Hussein, Mohd Zobir; Salleh, Abu Bakar; Raja Abdul Rahman, Raja Noor Zaliha (2007)
Lipase from Candida rugosa (CRL) was adsorbed onto three calcined layered double hydroxide (CLDH); Mg/Al-NO3 (CMAN), Ni/Al-NO3- (CNAN) and Zn/Al-NO3- (CZAN). Scanning Electron Microscopy-Energy Dispersive X-ray Spectroscopy (SEM-EDX) and protein staining-light microscopy analyses were applied to provide direct spectroscopic and microscopic evidence for the adsorption of CRL onto CLDH. SEM-EDX spectra show CRL presence in CMAN-CRL, CNAN-CRL and CZAN-CRL prepared. Blue spots on the surface of CMAN-CRL, CNAN-CRL and CZAN-CRL stained with Coomasie Blue R confirm protein adsorption onto supports. The catalytic activity of all three CLDH-CRL was also evaluated in synthesis of methyl caprylate and results showed that CMAN-CRL and CNAN-CRL exhibited 70 % conversion while CZAN-CRL exhibited 80 % conversion compared to free lipase that exhibited only 6 % conversion only.